2021
DOI: 10.1007/s00464-021-08405-1
|View full text |Cite
|
Sign up to set email alerts
|

Preaponeurotic endoscopic repair (REPA) of diastasis recti: a single surgeon’s experience

Abstract: Background Diastasis recti is a pathology that affects not only the abdominal wall but also the stability of lumbopelvic muscles, consequently altering urinary and digestive functionality. Preaponeurotic endoscopic repair (REPA) is an endoscopic alternative to tummy tuck for the treatment of diastasis. In this study, the outcomes of REPA application by a single surgeon are presented. Methods A total of 172 patients underwent REPA for the treatment of diastasis recti between August 2017 and December 2019. One h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Of the 56 included studies, 31 described open RD repairs (multiple studies described several approaches amounting to a total of 39 technical variations described) [12–42] while 28 studies described laparoscopic RD repairs [19, 38, 42–67]. Three studies described both open and laparoscopic repairs [19, 38, 42].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 56 included studies, 31 described open RD repairs (multiple studies described several approaches amounting to a total of 39 technical variations described) [12–42] while 28 studies described laparoscopic RD repairs [19, 38, 42–67]. Three studies described both open and laparoscopic repairs [19, 38, 42].…”
Section: Resultsmentioning
confidence: 99%
“…Sixty-three patients responded to a satisfaction and quality of life survey 12 months after surgery. It was concluded that endoscopic repair is safe and effective for the treatment of diastasis recti [28]. We consider the implemented methodology to be a strength, with respect to the literature search, selection of relevant articles, quality assessment and data extraction.…”
Section: Discussionmentioning
confidence: 99%
“…This MIS approach performing a subcutaneous dissection above the anterior rectus sheath has been described by different authors with several modifications [ 7 , 8 , 18 , 19 , 24 ] to this technique and we refer to it as ENDOR (Endoscopic Onlay Repair) in an attempt to utilize a standardized term. In regard to our technique, we perform an ENDOR for patients with BMI<30 to decrease the associated wound morbidities that we noticed from our initial experience with this approach.…”
Section: Discussionmentioning
confidence: 99%